The effect of replacing electrolytic iron in a multi-micronutrient fortification mix with sodium iron(III) ethylenediaminetetraacetate (NaFeEDTA) on the sensory properties of porridge from maize meal - De Kock, Henrietta Letitia (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.